Toward an Empirical Measure of Materiality - Rose, J.; Beaver, W.; Becker, S.; Sorter, G. (Journal of Accounting Research, 1970)
J. Rose, W. Beaver, S. Becker, G. Sorter, Toward an Empirical Measure of Materiality, Journal of Accounting Research, Vol. 8, Empirical Research in Accounting: Selected Studies 1970 (1970), pp. 138-148